Knittable and Washable Multifunctional MXene‐Coated Cellulose Yarns. (5th September 2019) - Uzun, Simge; Seyedin, Shayan; Stoltzfus, Amy L.; Levitt, Ariana S.; Alhabeb, Mohamed; Anayee, Mark; Strobel, Christina J.; Razal, Joselito M.; Dion, Genevieve; Gogotsi, Yury
Abstract: Textile‐based electronics enable the next generation of wearable devices, which have the potential to transform the architecture of consumer electronics. Highly conductive yarns that can be manufactured using industrial‐scale processing and be washed like everyday yarns are needed to fulfill the promise and rapid growth of the smart textile industry. By coating cellulose yarns with Ti3 C2 T x MXene, highly conductive and electroactive yarns are produced, which can be knitted into textiles using an industrial knitting machine. It is shown that yarns with MXene loading of ≈77 wt% (≈2.2 mg cm −1 ) have conductivity of up to 440 S cm −1 . After washing for 45 cycles at temperatures ranging from 30 to 80 °C, MXene‐coated cotton yarns exhibit a minimal increase in resistance while maintaining constant MXene loading. The MXene‐coated cotton yarn electrode offers a specific capacitance of 759.5 mF cm −1 at 2 mV s −1 . A fully knitted textile‐based capacitive pressure sensor is also prepared, which offers high sensitivity (gauge factor of ≈6.02), wide sensing range of up to ≈20% compression, and excellent cycling stability (2000 cycles at ≈14% compression strain). This work provides new and practical insights toward the development of platform technology that can integrate MXene in cellulose‐based yarns for textile‐based devices. Abstract : Knittable and washable MXene‐coated cellulose yarns are developed via a two‐step dip coating process for use in wearable applications. These conductive yarns, which combine the versatile chemistry and promising electrical and electrochemical properties of MXenes with existing cellulose‐based yarns, can offer a platform technology for various textile‐based devices by allowing tunability in performance for the building blocks of textiles.